English in China's universities : past and present - Bolton, Kingsley (2015)
By many, the recent popularity of English in Chinese education, at all levels of learning, has been seen as a very modern phenomenon, which followed the opening of China in the late 1970s. In fact, the learning of English in China has a long and partly forgotten history, not least at the level of higher education. From a historical perspective, it is salutary to remember that English medium universities and colleges were first established in China in the late 19th and early 20th century. Today, all the state-run key universities in China are officially Putonghua-medium, but despite that, English has an increasing presence in university education, both in the classroom and in the personal lives of Chinese university students.